Enantioselective Amination of β‐Keto Esters Catalyzed by Chiral Calcium Phosphates. Issue 37 (23rd May 2022) - Wu, Zhenwei; Krishnamurthy, Suvratha; Satyanarayana Tummalapalli, K. S.; Xu, Jun; Yue, Caizhen; Antilla, Jon C.
Abstract: A catalytic enantioselective amination of β ‐keto esters using ( S )‐BINOL chiral calcium phosphate has been developed. The reaction produces chiral α ‐amino‐ β ‐keto ester derivatives in most cases with moderate to excellent enantioselectivities (up to 99 %) and good yields (up to 99 %). This mild synthetic method highlights a low catalyst loading and high catalytic efficiency. When the substrate backbone was changed to 1‐tetralone‐derived β ‐keto esters, unexpectedly high yields of selective redox products were obtained. The practicality of the reaction was realized by a scale‐up without any significant loss in the enantioselectivity and yield. Chiral calcium phosphate was successfully recovered and reused for four runs, indicating its stability and high catalytic activity. Abstract : Chiral 2‐aminoindane derivatives are a relatively common structural motif found in natural products and pharmaceutical molecules. Hence its highly desirable to develop efficient synthetic methods for enantioselective amination of β ‐keto esters. A non‐toxic chiral calcium phosphate‐catalyzed enantioselective amination of β ‐ketoesters with dibenzyl azodicarboxylate has been developed, generating chiral α ‐amino‐ β ‐ketoester derivatives in good yields and moderate to excellent enantioselectivities under mild conditions.